Functional and structural analysis of double and triple mutants reveals the contribution of protein instability to clinical manifestations of G6PD variants - Praoparotai, A; Junkree, T; Imwong, M; Boonyuen, U (Elsevier, 2020)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common polymorphism and enzymopathy in humans, affecting approximately 400 million people worldwide. Over 200 point mutations have been identified in g6pd and the molecular mechanisms underlying the severity of G6PD variants differ. We report the detailed functional and structural characterization of 11 recombinant human G6PD variants: G6PD Asahi, G6PD A, G6PD Guadalajara, G6PD Acrokorinthos, G6PD Ananindeua, G6PD A-(202), G6PD Sierra Leone, G6PD A-(680), G6PD A-(968), G6PD Mount Sinai and G6PD No name. G6PD Guadalajara, G6PD Mount Sinai and G6PD No name are inactive variants and, correlating with the observed clinical manifestations, exhibit complete loss of enzyme activity. Protein structural instability, causing a reduction in catalytic efficiency, contributes to the clinical phenotypes of all variants. In double and triple mutants sharing the G6PD A mutation, we observed cooperative interaction between two and three mutations to cause protein dysfunction. The G6PD A (Asn126Asp) mutation exhibits no effect on protein activity and stability, indicating that the additional mutations in these G6PD variants significantly contribute to enzyme deficiency. We provide insight into the molecular basis of G6PD deficiency, which can explain the severity of clinical manifestations observed in individuals with G6PD deficiency.